Exploring isoxazoles and pyrrolidinones decorated with the 4, 6‐dimethoxy‐1, 3, 5‐triazine unit as human farnesyltransferase inhibitors. Issue 5 (4th April 2019) - Lucescu, Liliana; Ghinet, Alina; Shova, Sergiu; Magnez, Romain; Thuru, Xavier; Farce, Amaury; Rigo, Benoît; Belei, Dalila; Dubois, Joëlle; Bîcu, Elena
Abstract: Unprecedented triazinyl‐isoxazoles were afforded via an effective cycloaddition reaction between nitrile oxides and the scarcely described 2‐ethynyl‐4, 6‐dimethoxy‐1, 3, 5‐triazine as dipolarophile. The biological evaluation of the newly synthesized compounds showed that the inhibition of human farnesyltransferase by zinc complexation could be improved with triazine‐isoxazole moieties. The replacement of the isoxazole unit by a pyrrolidin‐2‐one was detrimental to the inhibitory activity while the pyrrolidin‐2‐thione derivatives conserved the biological potential. The potential of selected compounds to disrupt protein farnesylation in Chinese hamster ovary (CHO) cells transfected with pEGFP‐CAAX was also evaluated. Abstract : New triazinyl‐isoxazoles were generated via effective cycloaddition between nitrile oxides and 2‐ethynyl‐4, 6‐dimethoxy‐1, 3, 5‐triazine as dipolarophile. The triazine‐isoxazole moieties improved the inhibition of human farnesyltransferase by zinc complexation. Replacement of the isoxazole unit by a pyrrolidin‐2‐one was detrimental to the inhibitory activity while the pyrrolidin‐2‐thione derivatives conserved the biological potential.